Trade Liberalization May Be Harmful under Endogenous Differentiation - Luca Lambertini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1996)
The consequences of free trade are investigated in an international duopoly under horizontal differentiation and convex transportation costs. It is shown that the smaller country may benefit from trade if it is sufficiently small to allow for a significant volume of exports by the domestic firm. On the contrary, the larger country never benefits from trade, since liberalization decreases the domestic firm's profit more than it increases consumer surplus.
Keywords: 330